2021
DOI: 10.7150/thno.56747
|View full text |Cite
|
Sign up to set email alerts
|

The double-edged roles of ROS in cancer prevention and therapy

Abstract: Reactive oxygen species (ROS) serve as cell signaling molecules generated in oxidative metabolism and are associated with a number of human diseases. The reprogramming of redox metabolism induces abnormal accumulation of ROS in cancer cells. It has been widely accepted that ROS play opposite roles in tumor growth, metastasis and apoptosis according to their different distributions, concentrations and durations in specific subcellular structures. These double-edged roles in cancer progression include the ROS-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
246
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 372 publications
(253 citation statements)
references
References 248 publications
7
246
0
Order By: Relevance
“…In our previous study, we showed the dual roles of ROS in cancer progression: abnormal ROS accumulation induces malignant transformation, while excessive ROS levels that exceed a threshold lead to cell death 5 . We verified this point in LUAD cells and found that H 2 O 2 at a low concentration (≤20 μmol/L) promoted cellular proliferation, but H 2 O 2 at a high concentration (≥40 μmol/L) induced cell death (Figure 4A, C and E).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we showed the dual roles of ROS in cancer progression: abnormal ROS accumulation induces malignant transformation, while excessive ROS levels that exceed a threshold lead to cell death 5 . We verified this point in LUAD cells and found that H 2 O 2 at a low concentration (≤20 μmol/L) promoted cellular proliferation, but H 2 O 2 at a high concentration (≥40 μmol/L) induced cell death (Figure 4A, C and E).…”
Section: Resultsmentioning
confidence: 99%
“…H 2 O 2 is highly diffusible and enters the cytoplasm as a second messenger. Moderately increased ROS in hypoxic cancer cells could stabilize HIF-1α and mediate various tumorigenesis-associated signaling pathways, including AKT, NF-κB, AMPK and Notch 55 - 60 . Nevertheless, a vicious cycle between mitochondria damage and ROS generation could threaten the survival of hypoxic cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect of HO-1 expression in cancer cells is the gain of a resistant phenotype. It is well known that conventional anticancer treatments such as chemo- and radio- therapies can act to induce oxidative stress by increasing intracellular ROS levels [ 141 ] in order to favor apoptosis, as recently reviewed by Aggarwal and co-workers [ 142 ]. However, cancer cells, by up-regulating their antioxidant defenses, including HO-1, can counteract oxidative stress.…”
Section: Role Of Ho-1 In Cancer Progressionmentioning
confidence: 99%